Creative Economic Empowerment Policy in Supporting Tourism Potential in Banten Province - Zainuri, Ahmad (Indonesian Journal of Social Science Research, 2022)
The purpose of this study is to discuss creative economic empowerment policies in supporting tourism potential in Banten Province. The research method uses a qualitative descriptive research approach. The technique of determining the informants in this study was determined based on the purposive sampling technique through data collection techniques through observations, interviews and document searches. Data analysis techniques are carried out continuously during data collection in the field until data collection is completed. This analysis includes several activities, namely reviewing data, grouping data, finding what is important according to the research focus and studying and deciding what to report. The results of the study indicate that the policy of empowering the creative economy in supporting tourism potential is still not fully effective, based on the analysis of the ABCD (Asset Based Community Development) approach even though the changes have come from within the community but still have obstacles to existing capacities and assets in the community, relationships and orientation towards sustainable community growth.